Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T23:00:09+01:00
2x²+(x+8)(x-3)-2(x²+2,5x-15)=2x²+x²-3x+8x-24-2x²-5x+30=x²+6
x²+6--to wyrażenie jest dodatnie dla każdego x
2 5 2
  • Roma
  • Community Manager
2010-02-03T23:07:02+01:00
2x² + ( x + 8)(x - 3) - 2(x² + 2,5x - 15) > 0
2x² + x² - 3x + 8x - 24 - 2x² - 5x + 30 > 0
x² + 6 > 0
Δ = - 24 < 0
a = 1 > 0
x ∈ R
ZW = R+
2010-02-03T23:10:25+01:00
2x² + (x+8)(x-3)-2(x² + 2,5x - 15) = 2x² + x² - 3x + 8x - 24 - 2x² - 5x + 30 =
= x² + 6
Kwadrat każdej liczby jest nieujemny, więc wyrażenie (x² + 6) jest dodatnie.